(untitled) (Jurnal Pelita Pendidikan, 2016)
The study was implemented to improve learning outcomes and students activity in subject matter of cell with innovation learning throught combination of cooperative model of STAD (Student Teams Achievement Division) with Snowball throwing in Class XI MIA 5 SMA Negeri 5 Medan. This study is a classroom action research (CAR) is performed in two cycle research. This research was conducted by direct observation of teacher (researcher) and students. The observer implementation of research conducted by four research associates and biologys teacher in class XI MIA 5 SMA Negeri 5 Medan. Observations carried out on 35 students. Indicator of success research include: classical learning exhaustiveness and student activity observation. The result of this study indicate that the average value of the pretest students before the learning process carried out by using a combination cooperative model of STAD (Student Teams Achivement Division) with Snowball Throwing is 49,7 while the average in Postest I is 68,7. Exhaustiveness percentage of students studying in the cycle I amounting to 60%, this has yet to achieve exhaustiveness criterion in the clasiccal style because it has not reached â‰¥85%. In cyle II obtained the average value of student learning outcomes by 82,1 and there are 31 students who completed the criteria included in the study. Percentage of students in learning exhaustiveness second cyle is 88,5. Increase of classical learning completeness of cycle I to cycle II is 18%. Based on the average percentage of student who are active in cyle I and cycle II is obtained by increasing student activity in the cyle I mean the percentage level of activity of student is 62,85% and the second cyle increased to 85,71%. Increase student activity from cycle I to cyle II was 22,86%. As well as increased activity of teacher from 66,25% in cycle I increased to 86,25 in cycle II. Increase of teachers activity by 20%. From the above explanation, it can be concluded that this research can improve of learning outcomes and student activity. Keywords: Learning Outcomes, Student Activity, STAD (Student Teams Achievement Division), Snowball Throwing, Classroom Action Research.